146 Contribution of Conduction and Repolarisation Abnormalities to the Type i Brugada Pattern: A Study Using Non-Invasive Electrocardiographic Imaging. (3rd June 2016) - Leong, Kevin Ming Wei; Siong Ng, Fu; Yao, Cheng; Yates, Sian; Taraborrelli, Patricia; Linton, Nicholas W; Whinnett, Zachary; LeFroy, David; Davies, D Wyn; Lim, Phang Boon; Peters, Nicholas S; Harding, Sian E; et al.
Abstract : Introduction: In Brugada Syndrome (BrS), the substrate location and underlying electrophysiological mechanisms that contribute to the characteristic ECG pattern are still debated. Using non-invasive electrocardiographical imaging (ECGi), we study whole heart conduction and repolarisation patterns following an ajmaline challenge in individuals with concealed Type I BrS. Methods: 13 participants (mean age 44 ± 12 yrs; 8 males), 11 concealed Type I BrS and 2 controls, underwent an Ajmaline infusion with ECGI and ECG recordings for a research study. ECGi technology reconstructs >1000 electrograms (EGMs) from 252 surface electrode vest and projects this mathematically onto a 3D cardiac image created using a CT scan. Activation time points were determined as the QRS (dP/dtmin) and repolarisation time as (dP/dtmax) for positive T waves and (dp/dtmin) for negative or biphasic T waves, annotated using a custom built semi-automated software off-line. From these data, the local activation recovery interval (ARI), a surrogate of action potential duration, and activation timings across the right ventricle (RV) body, out flow tract (RVOT), and left ventricle (LV) were computed for all participants (Figure 1a ). Changes in AT timings and ARI across the RVOT, RV and LV with ajmaline were calculated, and correlated with peak ST elevation (STE) derived from the ECG at the same time point. Results: Following ajmaline administration, the greatest median increase in conduction delay was noted in the RVOT than in the RV or LV (5[3–8] ms vs 1[0–4]ms vs 1[0–2] ms; p < 0.0001) (FigURE 1b ). Prolongation of ARI was also observed to have increased the most in the RVOT (68[53–99] ms vs 35[23–46] ms vs 25[9–30] ms; p < 0.01). In the two control patients, no STE was noted with minimal rise in conduction delay or ARI prolongation noted in the RVOT, RV and LV. Only conduction delay in RVOT with ajamaline correlated to amount of STE (Pearson R 0.8, p < 0.001) (Figure 1c ), but not in the RV or LV (Pearson 0.3 and 0.2 respectively; p=ns). No significant correlation was also seen between STE and ARI prolongation in the RVOT, RV or LV (Pearson 0.5, 0.4, 0.1 respectively; p=ns). Conclusion: Magnitude of STE in the Type I BrS pattern is attributed to degree of conduction delay in the RVOT and not prolongation in repolarisation time.